Peran Moderasi Kepemilikan Institusional Terhadap Determinan Return On Equity Di Bursa Efek Indonesia - Surya Sanjaya; Jufrizen Jufrizen (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
This study aims to determine the effect of Cash Turnover, Turnover Turnover and Fixed Assets Turnover to Return On Equity (ROE) with Institutional Ownership as moderating variables either partially or simultaneously on the company Property and Real Estate listed in Indonesia Stock Exchange period 2011-2015. The approach of this research is the quantitative approach, population in this research is a company of Property and Real Estate which listed in Indonesia Stock Exchange year 2011-2015, sample in this research is determined by purposive sampling from 50 companies, and 14 companies that meet the criteria to be sampled research. The type of data in this study is secondary data. Analysis technique using multiple linear regression analysis. The results of this study show that partially Cash Turnover effect is not significant to Return On Equity. Receivable Turnover has no significant effect on Return On Equity and Institutional ownership does not moderate the influence of both. Fixed Assets Turn over significant effect on Return On Equity and moderate Institutional ownership. Simultaneously variable Cash Turnover, Receivable Turnover, and Fixed Assets Turnover significant effect on Return On Equity. Institutional Ownership has no significant effect on Return On Equity and Institutional Owners moderate the relationship between Cash Turnover, Accounts Receivable Turnover and Fixed Assets Turnover with Return on Equity. Ownership of Institutions as Moderating Variables in this study.